Equilibrium Contracts and Boundedly Rational Expectations - Heiner Schumacher; Heidi Thysen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We study an informed-principal framework in which the principal chooses the variables the agent is aware of. The agent fits a causal model connecting these variables to the objective probability distribution. The principal may keep her unaware of some variables so that she incorrectly extrapolates how non-equilibrium actions map into outcomes. This framework captures models of contracting with unaware agents, shrouded attributes, and overconfidence in a unified manner.
Keywords: D03; D82; D86; 330